2011
DOI: 10.1364/oe.19.018774
|View full text |Cite
|
Sign up to set email alerts
|

Electric and magnetic surface polariton mediated near-field radiative heat transfer between metamaterials made of silicon carbide particles

Abstract: Near-field radiative heat transfer between isotropic, dielectric-based metamaterials is analyzed. A potassium bromide host medium comprised of silicon carbide (SiC) spheres with a volume filling fraction of 0.4 is considered for the metamaterial. The relative electric permittivity and relative magnetic permeability of the metamaterial are modeled via the Clausius-Mossotti relations linking the macroscopic response of the medium with the polarizabilities of the spheres. We show for the first time that electric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 53 publications
0
47
0
Order By: Relevance
“…With today's nanofabrication techniques it is possible to manufacture artificial materials such as photonic band gap materials and metamaterials which exhibit very unusual material properties like negative refraction [23]. Due to such properties they are considered as good candidates for perfect lensing [24,25], for repulsive Casimir forces [26][27][28][29] and enhanced or tunable radiative heat flux at the nanoscale [18][19][20][30][31][32] to mention a few.There exists a class of uniaxial metamaterials for which the permittivity and permeability tensor elements are not all of the same sign [33]. In particular, for such materials the dispersion relation for the solutions of Helmholtz's equation inside the material is not an ellipsoid as for normal uniaxial materials [34] but a hyperboloid [35].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With today's nanofabrication techniques it is possible to manufacture artificial materials such as photonic band gap materials and metamaterials which exhibit very unusual material properties like negative refraction [23]. Due to such properties they are considered as good candidates for perfect lensing [24,25], for repulsive Casimir forces [26][27][28][29] and enhanced or tunable radiative heat flux at the nanoscale [18][19][20][30][31][32] to mention a few.There exists a class of uniaxial metamaterials for which the permittivity and permeability tensor elements are not all of the same sign [33]. In particular, for such materials the dispersion relation for the solutions of Helmholtz's equation inside the material is not an ellipsoid as for normal uniaxial materials [34] but a hyperboloid [35].…”
mentioning
confidence: 99%
“…The common paradigm is that the largest heat flux can be achieved when the materials support surface polaritons which will give a resonant energy transfer restricted to a small frequency band around the surface mode resonance frequency [3,4,12,13]. Many researchers have tried to find materials enhancing the nanoscale heat flux due to the contribution of the coupled surface modes by using layered materials [14,15], doped silicon [16,17], metamaterials [18][19][20], phase-change materials [21] and recently graphene [22].…”
mentioning
confidence: 99%
“…Figure 5 shows the temperature of sphere B as a function of time for both the resonant and non-resonant dielectric functions, and in the absence and presence of sphere C. For the calculations, the net heat rate Q net,in is integrated over a bandwidth of 0.02 eV. The analysis presented in this section could be extended to multiple spheres, which is important in the design of Mie resonance-based metamaterials for controlling thermal emission [61,68,69] and for understanding heating and cooling by near-field thermal radiation.…”
Section: Near-field Radiative Heat Transfer Between Three Spheresmentioning
confidence: 99%
“…Optical properties of materials doped with nanoparticles have been investigated before [12,13]. Experimental and analytical study of thermal coatings doped with nanoparticles such as Gonome et al [14,15] can also be found in literature.…”
Section: Introductionmentioning
confidence: 99%